Hubungan Paritas, Persepsi Risiko Dan Persepsi Manfaat Dengan Pemeriksaan Triple Eliminasi Pada Ibu Hamil - Syafaroh, Lintang; Arta Puspitasari, Nike; Reynie Purnama Raya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Triple Elimination is a government policy aimed at reducing the incidence of HIV, Syphilis, and Hepatitis B transmission from mother to child. Low coverage of Triple Elimination screening in Indonesia is partly due to pregnant women's lack of knowledge about the benefits of screening, stigma surrounding sexually transmitted infections, and a perception of low risk of those diseases.Objective: This study aims to analyze the association between parity, risk perception, and risk benefit with Triple Elimination screening among pregnant women.Methods: A quantitative cross-sectional study was conducted using quota sampling, involving 30 pregnant women as respondents. Data were collected through a structured questionnaire administered via the Google Form platform. Univariate analysis was used to describe respondent’s characteristics, independent variables (parity, risk perception, and benefit perception), and participation in the Triple Elimination screening. Bivariate analysis was performed using the Chi-Square test and Fisher’s Exact test.Results: Most respondents were aged 20–35 years (73.3%), had completed senior high school education (50.0%), were unemployed (66.7%), and had a good knowledge of the Triple Elimination program (86.7%). The majority had non-risk parity (76.7%), half had good risk perception (50.0%), and most had good benefit perception (73.3%). Participation in the Triple Elimination screening was recorded at 50%. Bivariate analysis showed that parity was not associated with participation in Triple Elimination screening (p=0.666), whereas perceived risk (p=0.011) and perceived benefit (p=0.002) were significantly associated with participation.Conclusion: There was no association between parity and participation in Triple Elimination screening. However, significant associations were observed between perceived risk and perceived benefit with screening participation. Future research is recommended to analyse all aspects of perception using the Health Belief Model framework.